Cooperative learning as a methodology to learn mechanical properties of materials in Civil Engineering - Rocio Porras Soriano; Juana Arias-Trujillo (Universitat Politècnica de València, 2016)
The current work presents an activity developed by first-year undergraduate students of Civil Engineering at the University of Castilla-La Mancha. Due to the character of this activity and the type of organisation of the students in small groups (3 people in each group), this activity can be defined as Cooperative Learning (CL). In this process, students must estimate by using an experimental design the Young's Modulus of a rubber elastic band, which has been previously delivered to the students by the professor. Before the beginning of this task, students have studied all the  necessary theoretical concepts to develop this experiment, however neither kind of extra indications have been given to them about how to resolve it, so that they should elucidate on their own a testing methodology which allow them to reach the goal of this task. This activity has been carried out for five years, and in spite of its non mandatory character, students have showed a great interest and motivation for it. Paying attention to several criteria such as evaluation, reached objectives or the involvement of the students. The results obtained from the activity have been highly satisfactory both for professors and students.The content of this document is structured as follow: first, the educational context is exposed including the development the subject and the most singular characteristics of the degree. After that, both the curriculum of the subject and the traditional way of teaching Elasticity are exposed. Moreover, it is described the learning strategy proposal and some of the solutions adopted by students. Finally, themost relevant conclusions are drawn.